Neutron reflectivity studies of the structure of polymer/polymer and polymer/substrate interfaces at the nanometer level - Sferrazza, M; Jones, R; Penfold, J; Bucknall, D; Webster, J (2000)
We review the use of neutron reflectivity as a probe of organic thin films, concentrating on its application to study buried interfaces in thin polymer films. For an interface between immiscible polymers of relatively low molecular weight, we find a width greater than that observed for higher molecular weight species, and we find that the width grows with time either logarithmically or following a weak power law. The conformation of a layer of very high molecular weight polymer chains chemically grafted to a silicon interface and coated by a chemically different polymer matrix is studied as a function of temperature, which controls the thermodynamic interaction between the grafted chains and the chemically different matrix chains. At high temperatures the layer abruptly changes from an extended conformation to one with a sharp interface with the matrix layer.